Clostridium sporogenes as surrogate for proteolytic C. botulinum - Development and validation of extensive growth and growth-boundary model. (October 2022) - Koukou, Ioulia; Stergioti, Thomai; la Cour, Rasmus; Gkogka, Elissavet; Dalgaard, Paw
Abstract: An extensive cardinal parameter growth and growth boundary model for C. sporogenes, as a surrogate for proteolytic C. botulinum, was developed to include the inhibitory effect of 11 environmental factors. 626 maximum specific growth rates ( μ max ) in broth were generated to determine cardinal parameter values for the growth inhibiting effect of temperature, pH, NaCl/water activity (aw ), organic acids (acetic, benzoic, citric, lactic, sorbic) and phosphate melting salts (ortho-, di- and tri-phosphates). μ max -values for C. sporogenes growing in well-characterized processed cheeses were used for product calibration (n = 10) and for product evaluation of the developed broth-model (n = 29). 112 growth/no-growth responses and including 104 μ max -values from the scientific literature for 58 different isolates of proteolytic and toxigenic C. botulinum (Group I) were used for further model evaluation. The developed model had less bias and a higher percentage of correct predictions than available models and was acceptable for processed cheese and good for meat products. The new and extensive model can predict combinations of environmental factors that prevent growth of C. sporogenes and of proteolytic C. botulinum . These predictions are expected to facilitate development or re-formulation of processed cheese and meat products where growth is prevented. Highlights: C. sporogenes growth model to support product development/re-formulation. Extensive model with 11 environmental factors. New model validated for processed cheese and meat products. Model performed better when compared with available proteolytic C. botulinum models.